Deconvolution of design parameters from elasto-plastic energy data acquired by nanoindentation in ceramic coatings - Castrillón Trujillo, Juan Carlos; Meza Meza, Juan Manuel (Scientia et Technica, 2017)
The elasto-plastic energies and the RID parameter (Relative Indentation Depth b=hmax/t), defined as the ratio between the maximum indentation depth and the coating thickness, were used to evaluate the ability of the ceramic coated systems to withstand load. The study was conducted on M2 and 304L steels coated with titanium nitride by PAPVD. Both substrates were coated with TiN of about 2,0 and 3,0 µm thickness. The hardness vs. (b) and the ratio of plastic to total energy (Wp/Wt) vs. (b) graphs were analyzed. There were found correlations between the indentation depths at which the transition from mechanical response due to the coating to the mechanical response of substrate-coating and to substrate dominated behavior and the depths at which the efficiency of using the coating falls 33% and 50 %. Results show that it is possible to get useful information from the energy taken from the mechanical response of the coated systems to avoid the Oliver and Pharr method for measuring the hardness and elastic modulus.